The Innovative Design of Rolling Stock Brake Elements - Gerlici, Juraj; Gorbunov, Mykola; Kravchenko, Kateryna; Prosvirova, Olga; Lack, Tomas (Communications - Scientific letters of the University of Zilina, 2017)
The paper deals with traffic safety in railway transport. The influence of the work of the braking system friction elements on braking performance is evaluated. The temperature in the pad-on-disc or pad-on-wheels contact has significant influence on the friction brake elements. Important factor in achieving maximum braking power is the control of the temperature in the contact. The analysis of methods and designs for heat dissipation from contact friction elements is carried out. The effect of ventilation channels of disc brakes on the vehicle running resistance is considered. The technical solutions for temperature control in friction elements during braking are proposed. Based on the analysis, an innovative solution of the brake disc was proposed. The proposed solution will reduce the wear of the friction surfaces, will significantly simplify the technological process of the brake disc replacement, will reduce the probability of cracks in the depth of the disc and will increase the reliability of its operation.